MENDAMPINGI KELOMPOK MASYARAKAT DESA TANJUNG MERIAH PASCA PKM DALAM MENJAGA KEBERLANGSUNGAN MESIN PENGUPAS PINANG - Eswanto Eswanto; Nurdiana Nurdiana; Jufrizal Jufrizal; Tony Siagian; Muhammad Razali; Husni Thamrin (LPPM Universitas Abdurrab, 2023)
In the village of Tanjung Meriah, Sitellu Tali Urang Jehe subdistrict, there are areca nut farmers who have the potential to increase the family's economy. The process of stripping areca nut from its fiber or skin is done traditionally using a makeshift machete. In the previous activity, a areca peeling machine was made using a machine, but currently it is constrained by periodic maintenance problems that need guidance. On this occasion, the areca nut farmers hope that the peeling of the areca nut will continue to run smoothly, of course, with the help of a machine, the stripping process will take a short time. The method of implementation is carried out by directly accompanying partners to practice how to maintain the areca peeler machine, starting with theory, machine demonstration and practice by each person in turn. The purpose of this activity is to provide knowledge on how to maintain the areca peeling machine after the community partnership program that was previously implemented, so that the community can maintain the continuity of the machine so that it can be used for a long time. The results of this program implementation have had a good impact on increasing partners' knowledge regarding the steps that must be taken in periodic engine maintenance. Another result that can be recommended to the Tanjung Meriah village community group is that they can make, develop their own without being accompanied by the PKM team because with sufficient knowledge from the results of the assistance that has been done before.